Produção de novilhos castrados ou não-castrados terminados em confinamento em idade jovem ou superjovem - Cullmann, Jacson Rodrigo (2016)
It was evaluated the productive performance and the yield of commercial cuts of the carcass of non-castrated or castrated slaughtered at a young age or young steers finished feedlot. The animals were fed a diet containing 11.2% crude protein and 3.07 Mcal of digestible energy / kg of dry matter, composed of 50% roughage and 50% concentrate. The initial age at the beginning of confinement of young steers and steers were 9 and 22 months, respectively. Greater PF was observed for non-castrated young animals (581.11 kg) in relation to young steers non-castrated, steers castrated and non-castrated (478.00, 455.22 and 437.29 kg, respectively). The ADG was 31% higher for the steers in relation to young steers. The DMI was 27% higher for steers on young steers and non-castrated consumed 9% more compared to the castrated. Most DMI per 100 kg of body weight was observed for the castrated steers (2.58 kg). The half-carcass weight difference between non-castrated and castrated animals was 43% for steers and 18% for young steers. Non-castrated showed higher forequarter percentage (8%). Higher percentage hacksaw cut was observed in castrated steers. Steers showed higher average daily gain weight, as well as non-castrated steers showed higher final weight. non-castrated animals have higher half cold carcass weights, front percentage and of edible portion of the front in relation to castrated.